Solubility of Poorly Soluble Drugs in Phosphatidylcholine-Based Drug Delivery Systems: Comparison of the Loading Capacity in the Bulk Formulation and Its Dispersed State - Linda Grüne; Heike Bunjes (Pharmaceuticals, 2024)
The aim of this study was to determine the drug loading capacity of phosphatidylcholine-based formulations for four poorly water-soluble drug substances (clofazimine, fenofibrate, artemether, cannabidiol). Two self-dispersing lipid formulations were investigated, which consisted of soybean phospholipids, medium-chain triglycerides and ethanol with a different phospholipid–oil ratio. The direct loading of the bulk formulation was conducted with dual centrifugation, which proved to be a suitable method for screening experiments with the highly viscous formulations. To estimate possible precipitation after dispersion in the gastrointestinal fluids, the solubility of the drugs was investigated in the dispersed formulations. For this purpose, nanodispersions were prepared from the bulk formulations via high pressure homogenization and subsequently subjected to passive loading. A newly developed HPLC method with Charged Aerosol Detection allowed a simultaneous evaluation of the content of soybean lecithin and medium-chain triglycerides in the nanodispersions. When comparing the two phosphatidylcholine-based formulations, a high content of oil was advantageous with regard to a high loading capacity. Drug substances with melting points below 150 °C exhibited a high solubility in the phospholipid-based formulations. A surprisingly high solubility was observed for artemether and cannabidiol with up to 13.0% and 33.3% drug loaded to the formulations, respectively. In the dispersions, a similar solubility as in the bulk formulations was obtained for fenofibrate and cannabidiol. Clofazimine yielded a higher loading result in the nanodispersions than in the bulk formulation.